Suture-related keratitis following cataract surgery caused by methicillin-resistant Staphylococcus aureus - Ahmad B Tarabishy (Dove Medical Press, 2010)
Ahmad B Tarabishy1, Thomas L Steinemann21Cole Eye Institute, Cleveland Clinic, Cleveland, OH, USA; 2Cornea and External Eye Disease, MetroHealth Medical Center, Case Western Reserve University, Cleveland, OH, USAAbstract: A 54-year old-man presented with a two-day history of severe pain and decreased vision. Examination revealed a corneal ulcer associated with a loose suture from cataract surgery done approximately two years ago. The suture was removed and the patient was started on topic antibiotic treatment with cefazolin and gentamycin. Cultures revealed methicillin-resistant Staphylococcus aureus (MRSA). The antibiotic regimen was changed to include vancomycin but the ulcer continued to progress. Three days later, the ulcer had perforated and an emergent corneal patch graft was performed. To our knowledge, this is the first reported case of suture-related MRSA keratitis after uncomplicated clear corneal cataract surgery.Keywords: keratitis, MRSA, suture, staphylococcus aureus